2019
DOI: 10.3390/catal9010039
|View full text |Cite
|
Sign up to set email alerts
|

Pt–Ni Seed-Core-Frame Hierarchical Nanostructures and Their Conversion to Nanoframes for Enhanced Methanol Electro-Oxidation

Abstract: Pt–Ni nanostructures are a class of important electrocatalysts for polymer electrolyte membrane fuel cells. This work reports a systematic study on the reaction mechanism of the formation of Pt–Ni seed-core-frame nanostructures via the seeded co-reduction method involving the Pt seeds and selective co-reduced deposition of Pt and Ni. The resultant structure consists of a branched Pt ultrafine seed coated with a pure Ni as rhombic dodecahedral core and selective deposition of Pt on the edges of the cores. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
(62 reference statements)
1
8
0
Order By: Relevance
“…Therefore, it is For comparing the obtained results with the literature, a comparison table was added. Table 2 summarizes the comparison between the characteristics of the prepared modified carbon paste electrode and some previously modified electrodes [36][37][38][39]. As shown, the prepared modified electrode in this research has acceptable performance for methanol oxidation in acidic medium compared to other ones.…”
Section: The Ni-mmt/cpe Ability In Re-oxidation Of Methanolmentioning
confidence: 79%
“…Therefore, it is For comparing the obtained results with the literature, a comparison table was added. Table 2 summarizes the comparison between the characteristics of the prepared modified carbon paste electrode and some previously modified electrodes [36][37][38][39]. As shown, the prepared modified electrode in this research has acceptable performance for methanol oxidation in acidic medium compared to other ones.…”
Section: The Ni-mmt/cpe Ability In Re-oxidation Of Methanolmentioning
confidence: 79%
“…Chen et al (2019) studied the reaction procedure of seeded co-reduction for the fabrication of PtNi seeded core frame structures. By controlling the shape of seeds, rhombic dodecahedra structures were obtained by depositing the Pt on their corners and edges.…”
Section: Synthetic Methodologies For Nanoframesmentioning
confidence: 99%
“…To further improve the ORR catalytic performance of the PtNi nanoparticles, tailoring their architecture becomes inevitable . Throughout the recent years, a variety of PtNi nanostructures have been reported, such as branched particles, , double dumbell, core–shell, hyperbranched nanostructures, octahedron, ,, dodecahedron, icosahedron, hexapods, nanocages, octahedral nanoframes, dodecahedral nanoframes, ,,, and multiframes …”
Section: Introductionmentioning
confidence: 99%
“…Previously, Chen et al developed a thermal evolution method to synthesize Pt 3 Ni polyhedral nanoparticles and dodecahedral nanoframes, and their ORR activities show the following order: Pt/C < PtNi polyhedra/C ≪ Pt 3 Ni nanoframes . Chen et al also demonstrated that PtNi nanoframes exhibited an enhanced ethanol electro-oxidation activity and stability than the Pt–Ni seed-core-frame nanostructures …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation